THE RELATIONSHIP BETWEEN SELF REGULATED LEARNING AND PEER CONFORMITY, ACADEMIC ANXIETY OF STUDENTS AT SMK NEGERI 3 PADANG - Biasri Suarim; Afdal (CV. Radja Publika, 2023)
This research is motivated by a phenomenon that occurs at SMK Negeri 3 Padang, namely low academic anxiety. Self-regulated learning and peer conformity are factors that influence students' academic anxiety. This study aims to analyze (1) self-regulated learning, (2) peer conformity, (3) academic anxiety, (4) self-regulated learning with students' academic anxiety, (5) the relationship between peer conformity and students' academic anxiety and (6) ) the relationship between self-regulated learning and peer conformity with students' academic anxiety. The research method used is quantitative. This type of research is descriptive correlational. The population in this research is 1047 students and the sample of this research is 290 students. Sampling used the Slovin formula and sampling using proportional random sampling technique. The research instrument was a questionnaire with a Likert Scale measurement. Data were analyzed with correlational descriptive statistics with the help of SPSS version 20.00. The results of the study show that (1) students' self-regulated learning is in medium, (2) peer conformity is in the medium category, (3) students' academic anxiety is in the r category, low (4) there is a positive relationship and significant between self-regulated learning and academic anxiety beliefs, (5) there is a positive and significant relationship between peer conformity and students' academic anxiety, and (6) there is a positive and significant relationship between self-regulated learning and peer conformity support with anxiety student academic. So it can be concluded that there is a positive and significant relationship between self-regulated learning and conformity of seabya friends with students' academic anxiety.